The Representation of Parenting Based on Sharenting (Semiotic Analysis of Roland Barthes on the TikTok Account @IDAWIDA) - Diana Yemima; Merry Fridha Tri Palupi; Herlina Kusumaningrum (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2023)
The development of digital technology has made the practice of sharenting popular among the public, including public figures and ordinary people. This phenomenon occurs because the ease and sophistication of technology allow them to quickly and easily share information. Sharenting refers to the act of sharing information about children on social media. This research aims to analyze the representation of sharenting-based parenting on the TikTok account @Idawida, which is the caregiver of celebrity child Gala Sky. In this study, Stuart Hall's theory of representation is used to understand the social and symbolic meanings in sharenting representations, while Roland Barthes' semiotic analysis method is used to analyze @Idawida's content for the past 6 months. The results of the analysis show that sharenting representations include video content of Idawida's interactions with Gala Sky, as well as elements such as captions, viewers, likes, and top comments. Connotations involve symbolic and social meanings, such as intimacy, harmony, popularity, and positive perceptions of Gala Sky by followers. However, there are also negative myths, such as unawareness about sharenting and unconscious exploitation. Additionally, the ideology found is the exploitation of Gala Sky's popularity for financial gain. Therefore, the recommendations from this research are to increase TikTok users' awareness of the implications of sharenting and develop policies that protect the privacy and interests of children on social media.